A garden of forking paths: an ecosystem-based fisheries management case study of Florida red tides - Brendan D. Turley; Skyler R. Sagarese; Mandy Karnauskas; Suzana D. Blake; Matthew McPherson; David D. Chagaris; Christopher R. Kelble (Reviews in Fish Biology and Fisheries, 2026)
Ecosystem-based fisheries management is a crucial advancement to address natural and anthropogenic stressors on marine ecosystems. Although there has been a shift toward more holistic management approaches over the past few decades, Fishery Management Councils still face challenges in implementing ecosystem-based strategies. Here, we present a case study on incorporating harmful algal blooms, known as red tides, into U.S. federal fisheries management on the West Florida Shelf. Red tides are first defined as a fishery ecosystem issue by outlining their ecological, economic, and societal impacts on the relevant fisheries. We then review the history of including red tides in the stock assessment process and how management actions have responded to episodic mortality attributed to devastating red tides. Fishery managers have encountered significant challenges when addressing red tides because the root causes are beyond fisheries management jurisdiction. The primary method to account for red tides in fisheries management has been to incorporate extra mortality in stock assessments. While integrating ecosystem information can reduce scientific uncertainty in stock assessments, the setting of catch limits also benefits from such information. Red tide-related management actions have been reactive, and frequent reversals of catch advice highlight the complexity of red tide impacts. The directionality of catch advice for Gulf groupers has been dependent upon additional information such as ecosystem modeling results and stakeholder observations. We offer a review of potential fishery management policy options that include, but are not limited to, the management of fishing mortality. We outline research recommendations to better characterize impacts and inform fisheries management’s response to red tides. Effective ecosystem-based fisheries management necessitates a clear definition of the problem, goals, expectations, metrics to measure progress, and a work plan that includes stakeholder engagement.

Diagnosis of Mycobacteriosis in Cultured Hybrid Tilapia ( Oreochromis spp.) in Trinidad and Tobago - Lemar Blake; Arianne Brown Jordan; Soren Nicholls; Esteban Soto; Luke Iwanowicz; Rod Suepaul; Christopher Oura; Ayanna Carla N. Phillips Savage (Journal of Fish Diseases, 2026)
Mycobacteriosis is a significant disease in fish husbandry, with negative impacts on production facilities. Moreover, some Mycobacterium spp. that infect fish have zoonotic potential. Morbidity and mortality events at hybrid tilapia ( Oreochromis spp.) farms in Trinidad and Tobago (T&T) associated with mycobacterial infections prompted a broader surveillance investigation across the hybrid tilapia farms within the country. Of the 168 specimens examined by polymerase chain reaction (PCR), 42% were Mycobacterium spp . positive. Among the mycobacteria‐positive specimens, clinical signs (lethargy and loss of equilibrium) were observed in 96% (68 of 71), of which gross external abnormalities were evident in 7% (5 of 68) and internal lesions (granulomas) in 22% (15 of 68). Specimens that were mycobacteria‐negative showed no clinical signs, gross abnormalities or lesions. Sequence analysis of a partial 723‐bp rpoB (region V) fragment confirmed the presence of a consortium of uncharacterised Mycobacterium spp. in 18 hybrid tilapia specimens. These findings suggest that potentially novel species are circulating within and causing clinical and subclinical disease in the local farmed hybrid tilapia population in T&T. The study also revealed that over the period 2020–2021, 75% (9 of 12) of the major hybrid tilapia production facilities in T&T were infected with mycobacteria. This represents the first documentation of a piscine mycobacteriosis outbreak in hybrid tilapia in the Caribbean.

Public health risks from potable water supply disruptions during drought in high-income countries: A scoping review and policy implications for the United Kingdom - Daniel Mark Blake; Joanna Orr; Kirsty Morrison; Anh Tran; Paul Christopher Coleman; Grace Anne Turner; Lauren Hands; Katya Brooks (International Journal of Hygiene and Environmental Health, 2026)

Brightness, colour, polarisation: a multi-instrument observation campaign of the Gorizont-6 satellite - Robert J.S. Airey; Paul Chote; Klaas Wiersema; Ioannis Apergis; James McCormac; James A. Blake; Benjamin F. Cooke; Isobel S. Lockley; Peter J. Wheatley; Daniel Bayliss; Samuel Gill; Christopher A. Watson; et al. (Advances in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Novel commensal rhizobacteria isolated from field-grown canola plants - Christopher Blake; Storme de Scally; John Pascoe; Atharva Bhide; Aysha L. Sezmis; Perran L.M. Cook; Vanessa N.L. Wong; Harsh Raman; Michael J. McDonald (Biocatalysis and Agricultural Biotechnology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

The finite element neural network method: One-dimensional study - Mohammed Abda; Mohsen Hamedi; Elsa Piollet; Christopher Blake; Frédérick P․Gosselin (Next Research, 2025)

Winter-Spring dynamics of dissolved organic carbon fluxes driven by precipitation in a North Carolina tidal marsh - Marie Cindy Lebrasse; Blake A. Schaeffer; DelWayne R. Bohnenstiehl; Christopher L. Osburn; Megan M. Coffer; Ruoying He; Peter J. Whitman; Wilson B. Salls; David D. Graybill (Estuarine, Coastal and Shelf Science, 2025)

Sediment and soil source apportionment using geochemical fingerprinting techniques in the Winam Gulf, Lake Victoria - Olivier S. Humphrey; Job Isaboke; Odipo Osano; Christopher Mulanda Aura; William H. Blake; Michael J. Watts (CATENA, 2025)

Confronting the interconnection of chemical pollution and climate change - Simona A. Bălan; Saskia K. van Bergen; Ann Blake; Topher Buck; Scott Coffin; Jamie C. DeWitt; Gretta Goldenman; Frank A. von Hippel; Sophia von Hippel; Christopher P. Leonetti; David Rist; Martin Scheringer; et al. (Environmental Innovation and Societal Transitions, 2025)

Identification of Potentially Novel Mycobacterium Spp. In Freshwater Ornamental Fish in Trinidad and Tobago - Lemar Blake; Arianne Brown Jordan; Soren Nicholls; Esteban Soto; Luke Iwanowicz; Rod Suepaul; Christopher Oura; Ayanna Carla N. Phillips Savage (Journal of Fish Diseases, 2025)
Potentially zoonotic Mycobacterium spp. are impacting freshwater ornamental fish in Trinidad and Tobago. Clinical cases presented at the Aquatic Animal Health Unit of The University of the West Indies, School of Veterinary Medicine, from September 2011 to September 2018 indicated the presence of piscine mycobacteriosis in freshwater ornamental fish from locations throughout Trinidad and Tobago. Subsequently, an investigation was conducted from June 2018 to December 2021 to identify the specific Mycobacterium spp. involved. Nested polymerase chain reaction (PCR) was used to amplify and later sequence the 723 bp of the rpoB. Analysis of region V of the rpoB offers similar discriminatory power as concatenation or whole genome analysis of Mycobacterium spp., and serves as an acceptable method for differentiating and discriminating between species in this genus. With respect to tank‐reared freshwater ornamental fish, this study identified M. fortuitum (98.8% identity), M. liflandii (100% identity), M. stomatepiae (97.2% identity), M. pseudoshottsii related (96.9% identity), two M. stomatepiae related (95.4% and 96.7% identity), M. immunogenum related (93.4% identity), and 17 M. insubricum related (91.4%–95.2% identity). Additionally, seven mycobacteria related to M. insubricum were identified in wild‐caught guppies. These findings suggest that both known, and potentially novel Mycobacterium spp. are circulating, and adversely impacting the local populations of freshwater ornamental fish in Trinidad and Tobago.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Co‐Existence Slows Diversification in Experimental Populations of E. coli and P. fluorescens - Gareth Howells; Aysha L. Sezmis; Christopher Blake; Michael J. McDonald (Environmental Microbiology, 2025)
Microbes grown in heterogeneous laboratory environments can rapidly diversify into multiple, coexisting variants. While the genetic and evolutionary mechanisms of laboratory adaptive radiations are well studied, how the presence of other species alters the outcomes of diversification is less well understood. To test the effect of co‐culture growth on the Pseudomonas fluorescens SBW25 adaptive radiation, Escherichia coli and P. fluorescens were cultured in monoculture and co‐culture for 8 weeks. In P. fluorescens monoculture, Wrinkly and Smooth Spreader types rapidly evolved and were maintained over 8 weeks, while E. coli monocultures evolved two colony types, a big and a small colony variant. In contrast, we found that in co‐culture, E. coli did not evolve small colony variants. Whole genome sequencing revealed the genetic basis of possible co‐culture specific adaptations in both E. coli and P. fluorescens . Altogether, our data support that the presence of multiple species changed the outcome of adaptive radiation.

A deep dive into the waterbird community of an urban oasis: implications for park management - August Wise; Anya Rosener; Arina Martin; Melissa Cote; Christopher D. Hopwood; Elizabeth Schwartz; Riley Tharp; Stephen Blake (Urban Ecosystems, 2024)

Microvertebrates from the Lower Greensand Group (Lower Cretaceous) of Clophill, Bedfordshire, UK, and Nutfield, Surrey, UK - Lila Blake; Max Fursman; Christopher J. Duffin; Trevor Batchelor; Claudia Hildebrandt; Michael J. Benton (Proceedings of the Geologists' Association, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Air quality trends for the ports of Los Angeles and Long Beach spanning the covid19 crisis: Part 1. Oxidant pollutants - Ira Leifer; Christopher Melton; Donald R. Blake; Simone Meinardi; Michael Kleinman (Atmospheric Environment, 2023)

Geoethical issues around water security for the City of Cape Town (South Africa) and groundwater resilience in uncertain circumstances: development of the Atlantis, Cape Flats and Table Mountain Group Aquifers - Dylan Blake; Christopher J. H. Hartnady; E. Rowena Hay; David C. McGibbon; Luke C. Towers; Kornelius Riemann; Rui T. Hugman (Sustainable Water Resources Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Changes in micronutrient concentrations under minimum tillage and cotton-based crop rotations in irrigated Vertisols - Blake Palmer; Christopher Guppy; Gunasekhar Nachimuthu; Nilantha Hulugalle (Soil and Tillage Research, 2023)

Effects of human-induced habitat changes on site-use patterns in large Amazonian Forest mammals - Simón Quintero; Mark I. Abrahams; Christopher Beirne; John Blake; Elildo Carvalho; Hugo C.M. Costa; Milton José de Paula; Whaldener Endo; Torbjørn Haugaasen; Marcela Guimarães Moreira Lima; Fernanda Michalski; Diego Mosquera; et al. (Biological Conservation, 2023)

Development of a Benchmark Eddy Flux Evapotranspiration Dataset for Evaluation of Satellite-Driven Evapotranspiration Models Over the CONUS - John M. Volk; Justin Huntington; Forrest S. Melton; Richard Allen; Martha C. Anderson; Joshua B. Fisher; Ayse Kilic; Gabriel Senay; Gregory Halverson; Kyle Knipper; Blake Minor; Christopher Pearson; et al. (Agricultural and Forest Meteorology, 2023)

Comparison study of ductile iron produced with Martian regolith harvested iron from ionic liquids and Bosch byproduct carbon for in-situ resource utilization versus commercially available 65-45-12 ductile iron - Blake C. Stewart; Haley R. Doude; Shiraz Mujahid; Morgan B. Abney; Eric T. Fox; Jennifer E. Edmunson; Jeffrey J. Mehan; Christopher R. Henry; Phillip B. Hall; Haitham El Kadiri; Hongjoo Rhee (Advances in Space Research, 2023)

Revealing oxidative pentose metabolism in new Pseudomonas putida isolates - Mee‐Rye Park; Rahul Gauttam; Bonnie Fong; Yan Chen; Hyun Gyu Lim; Adam M. Feist; Aindrila Mukhopadhyay; Christopher J. Petzold; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2023)
The Pseudomonas putida group in the Gammaproteobacteria has been intensively studied for bioremediation and plant growth promotion. Members of this group have recently emerged as promising hosts to convert intermediates derived from plant biomass to biofuels and biochemicals. However, most strains of P. putida cannot metabolize pentose sugars derived from hemicellulose. Here, we describe three isolates that provide a broader view of the pentose sugar catabolism in the P. putida group. One of these isolates clusters with the well‐characterized P. alloputida KT2440 (Strain BP6); the second isolate clustered with plant growth‐promoting strain P. putida W619 (Strain M2), while the third isolate represents a new species in the group (Strain BP8). Each of these isolates possessed homologous genes for oxidative xylose catabolism ( xylDXA ) and a potential xylonate transporter. Strain M2 grew on arabinose and had genes for oxidative arabinose catabolism ( araDXA ). A CRISPR interference (CRISPRi) system was developed for strain M2 and identified conditionally essential genes for xylose growth. A glucose dehydrogenase was found to be responsible for initial oxidation of xylose and arabinose in strain M2. These isolates have illuminated inherent diversity in pentose catabolism in the P. putida group and may provide alternative hosts for biomass conversion.

Temporal Stability of Seagrass Extent, Leaf Area, and Carbon Storage in St. Joseph Bay, Florida: a Semi-automated Remote Sensing Analysis - Marie Cindy Lebrasse; Blake A. Schaeffer; Megan M. Coffer; Peter J. Whitman; Richard C. Zimmerman; Victoria J. Hill; Kazi A. Islam; Jiang Li; Christopher L. Osburn (Estuaries and Coasts, 2022)
Seagrasses are globally recognized for their contribution to blue carbon sequestration. However, accurate quantification of their carbon storage capacity remains uncertain due, in part, to an incomplete inventory of global seagrass extent and assessment of its temporal variability. Furthermore, seagrasses are undergoing significant decline globally, which highlights the urgent need to develop change detection techniques applicable to both the scale of loss and the spatial complexity of coastal environments. This study applied a deep learning algorithm to a 30-year time series of Landsat 5 through 8 imagery to quantify seagrass extent, leaf area index (LAI), and belowground organic carbon (BGC) in St. Joseph Bay, Florida, between 1990 and 2020. Consistent with previous field-based observations regarding stability of seagrass extent throughout St. Joseph Bay, there was no temporal trend in seagrass extent (23 ± 3 km 2 , τ = 0.09, p = 0.59, n = 31), LAI (1.6 ± 0.2, τ = -0.13, p = 0.42, n = 31), or BGC (165 ± 19 g C m −2 , τ = - 0.01, p = 0.1, n = 31) over the 30-year study period. There were, however, six brief declines in seagrass extent between the years 2004 and 2019 following tropical cyclones, from which seagrasses recovered rapidly. Fine-scale interannual variability in seagrass extent, LAI, and BGC was unrelated to sea surface temperature or to climate variability associated with the El Niño-Southern Oscillation or the North Atlantic Oscillation. Although our temporal assessment showed that seagrass and its belowground carbon were stable in St. Joseph Bay from 1990 to 2020, forecasts suggest that environmental and climate pressures are ongoing, which highlights the importance of the method and time series presented here as a valuable tool to quantify decadal-scale variability in seagrass dynamics. Perhaps more importantly, our results can serve as a baseline against which we can monitor future change in seagrass communities and their blue carbon.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Piscine mycobacteriosis in the ornamental fish trade in Trinidad and Tobago - Ayanna Carla N. Phillips Savage; Lemar Blake; Rod Suepaul; O’Shane McHugh; Ray Rodgers; Calvern Thomas; Christopher Oura; Esteban Soto (Journal of Fish Diseases, 2022)
The freshwater ornamental fish trade represents a major contributor to the livelihoods of many producers in Trinidad and Tobago, with stocks destined for local, regional and international markets. A review of clinical cases presented to the Aquatic Animal Health Unit at the University of the West Indies, School of Veterinary Medicine for the period September 2010 to December 2012 suggested that piscine mycobacteriosis may be widespread throughout the local ornamental fish industry. Thus, to determine the prevalence of mycobacteriosis in ornamental fish sold in pet stores, a total of 122 specimens were sourced from 24 retail suppliers across Trinidad. Fish were killed and internal organs were examined for lesions suggestive of granulomas. All wet‐mount slides were acid‐fast stained, regardless of the presence or absence of observed granuloma‐like lesions. Histological analysis was performed on one randomly selected whole specimen from each facility. Mycobacterium sp. was identified using real‐time PCR detecting the 16S rRNA gene in tissue samples. Associations between parasitism, facility biosecurity and presence of positive animals were determined. The prevalence of Mycobacterium sp. infection was 61 ± 7% (74/122), with positive specimens being acquired from 54.2% (13/24) of facilities examined. Further, 100% of facilities did not employ optimum biosecurity measures.

Diversification of Bacillus subtilis during experimental evolution on A rabidopsis thaliana and the complementarity in root colonization of evolved subpopulations - Christopher Blake; Mathilde Nordgaard; Gergely Maróti; Ákos T. Kovács (Environmental Microbiology, 2021)
Summary The soil bacterium Bacillus subtilis is known to suppress pathogens as well as promote plant growth. However, in order to fully exploit the potential as natural fertilizer, we need a better understanding of the interactions between B. subtilis and plants. Here, B. subtilis was examined for root colonization through experimental evolution on Arabidopsis thaliana . The populations evolved rapidly, improved in root colonization and diversified into three distinct morphotypes. In order to better understand the adaptation that had taken place, single evolved isolates from the final transfer were randomly selected for further characterization, revealing changes in growth and pellicle formation in medium supplemented with plant polysaccharides. Intriguingly, certain evolved isolates showed improved root colonization only on the plant species they evolved on, but not on another plant species, namely tomato, suggesting A. thaliana specific adaption paths. Finally, the mix performed better than the sum of its constituents in monoculture, which was demonstrated to be caused by complementarity effects. Our results suggest that genetic diversification occurs in an ecological relevant setting on plant roots and proves to be a stable strategy for root colonization.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Using Full and Partial Unmixing Algorithms to Estimate the Inundation Extent of Small, Isolated Stock Ponds in an Arid Landscape - Christopher J. Jarchow; Brent H. Sigafus; Erin Muths; Blake R. Hossack (Wetlands, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Plant invasion into high elevations implies adaptation to high UV-B environments: a multi-species experiment - Lena Y. Watermann; Maria Hock; Christopher Blake; Alexandra Erfmeier (Biological Invasions, 2020)

Efficient Computational Modeling of Human Ventricular Activation and Its Electrocardiographic Representation: A Sensitivity Study - Jonathan P. Cranford; Thomas J. O’Hara; Christopher T. Villongco; Omar M. Hafez; Robert C. Blake; Joseph Loscalzo; Jean-Luc Fattebert; David F. Richards; Xiaohua Zhang; James N. Glosli; Andrew D. McCulloch; David E. Krummen; et al. (Cardiovascular Engineering and Technology, 2018)

Seroprevalence of economically important viral pathogens in swine populations of Trinidad and Tobago, West Indies - Jamie R. V. Sookhoo; Arianne Brown-Jordan; Lemar Blake; Ridley B. Holder; Sharon M. Brookes; Stephen Essen; Christine V. F. Carrington; Ian H. Brown; Christopher A. L. Oura (Tropical Animal Health and Production, 2017)

Post-absorptive muscle protein turnover affects resistance training hypertrophy - Paul T. Reidy; Michael S. Borack; Melissa M. Markofski; Jared M. Dickinson; Christopher S. Fry; Rachel R. Deer; Elena Volpi; Blake B. Rasmussen (European Journal of Applied Physiology, 2017)

Rare taxa have potential to make metabolic contributions in enhanced biological phosphorus removal ecosystems - Christopher E. Lawson; Blake J. Strachan; Niels W. Hanson; Aria S. Hahn; Eric R. Hall; Barry Rabinowitz; Donald S. Mavinic; William D. Ramey; Steven J. Hallam (Environmental Microbiology, 2015)
Summary Enhanced biological phosphorus removal ( EBPR ) relies on diverse but specialized microbial communities to mediate the cycling and ultimate removal of phosphorus from municipal wastewaters. However, little is known about microbial activity and dynamics in relation to process fluctuations in EBPR ecosystems. Here, we monitored temporal changes in microbial community structure and potential activity across each bioreactor zone in a pilot‐scale EBPR treatment plant by examining the ratio of small subunit ribosomal RNA ( SSU r RNA ) to SSU r RNA gene (r DNA ) over a 120 day study period. Although the majority of operational taxonomic units ( OTUs ) in the EBPR ecosystem were rare, many maintained high potential activities based on SSU r RNA : r DNA ratios, suggesting that rare OTUs contribute substantially to protein synthesis potential in EBPR ecosystems. Few significant differences in OTU abundance and activity were observed between bioreactor redox zones, although differences in temporal activity were observed among phylogenetically cohesive OTUs . Moreover, observed temporal activity patterns could not be explained by measured process parameters, suggesting that other ecological drivers, such as grazing or viral lysis, modulated community interactions. Taken together, these results point towards complex interactions selected for within the EBPR ecosystem and highlight a previously unrecognized functional potential among low abundance microorganisms in engineered ecosystems.

Acute Methylenedioxypyrovalerone Toxicity - Blake A. Froberg; Michael Levine; Michael C. Beuhler; Bryan S. Judge; Philip W. Moore; Kristin M. Engebretsen; Nathanael J. Mckeown; Christopher D. Rosenbaum; Amy C. Young; Daniel E. Rusyniak (Journal of Medical Toxicology, 2015)

Bacterial Community Composition of Three Candidate Insect Vectors of Palm Phytoplasma (Texas Phoenix Palm Decline and Lethal Yellowing) - Christopher M. Powell; Daymon Hail; Julia Potocnjak; J. Delton Hanson; Susan H. Halbert; Blake R. Bextine (Current Microbiology, 2015)

A Case of Abrin Toxin Poisoning, Confirmed via Quantitation of l-Abrine (N-Methyl-l-Tryptophan) Biomarker - Joe Valentine Wooten; Christopher T. Pittman; Thomas A. Blake; Jerry D. Thomas; John J. Devlin; Renee A. Higgerson; Rudolph C. Johnson (Journal of Medical Toxicology, 2014)

Bacterial Community Survey of Solenopsis invicta Buren (Red imported fire Ant) Colonies in the Presence and Absence of Solenopsis invicta Virus (SINV) - Christopher M. Powell; John D. Hanson; Blake R. Bextine (Current Microbiology, 2014)

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

Effects of Amphibian Chytrid Fungus on Individual Survival Probability in Wild Boreal Toads - DAVID S. PILLIOD; ERIN MUTHS; RICK D. SCHERER; PAUL E. BARTELT; PAUL STEPHEN CORN; BLAKE R. HOSSACK; BRAD A. LAMBERT; REBECCA MCCAFFERY; CHRISTOPHER GAUGHAN (Conservation Biology, 2010)
Chytridiomycosis is linked to the worldwide decline of amphibians, yet little is known about the demographic effects of the disease. We collected capture–recapture data on three populations of boreal toads ( Bufo boreas [Bufo = Anaxyrus] ) in the Rocky Mountains (U.S.A.). Two of the populations were infected with chytridiomycosis and one was not. We examined the effect of the presence of amphibian chytrid fungus (Batrachochytrium dendrobatidis [Bd]; the agent of chytridiomycosis) on survival probability and population growth rate. Toads that were infected with Bd had lower average annual survival probability than uninfected individuals at sites where Bd was detected, which suggests chytridiomycosis may reduce survival by 31–42% in wild boreal toads. Toads that were negative for Bd at infected sites had survival probabilities comparable to toads at the uninfected site. Evidence that environmental covariates (particularly cold temperatures during the breeding season) influenced toad survival was weak. The number of individuals in diseased populations declined by 5–7%/year over the 6 years of the study, whereas the uninfected population had comparatively stable population growth. Our data suggest that the presence of Bd in these toad populations is not causing rapid population declines. Rather, chytridiomycosis appears to be functioning as a low‐level, chronic disease whereby some infected individuals survive but the overall population effects are still negative. Our results show that some amphibian populations may be coexisting with Bd and highlight the importance of quantitative assessments of survival in diseased animal populations.

A nonsynonymous SNP within PCDH15 is associated with lipid traits in familial combined hyperlipidemia - Adriana Huertas-Vazquez; Christopher L. Plaisier; Ruishuang Geng; Blake E. Haas; Jenny Lee; Marleen M. Greevenbroek; Carla van der Kallen; Tjerk W. A. de Bruin; Marja-Riitta Taskinen; Kumar N. Alagramam; Päivi Pajukanta (Human Genetics, 2010)

Differentially expressed genes during malting and correlation with malting quality phenotypes in barley (Hordeum vulgare L.) - Nora L. V. Lapitan; Ann Hess; Blake Cooper; Anna-Maria Botha; Deborah Badillo; Hari Iyer; Jolanta Menert; Timothy Close; Les Wright; Gary Hanning; M. Tahir; Christopher Lawrence (Theoretical and Applied Genetics, 2009)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Photochemistry in the Arctic Free Troposphere: Ozone Budget and Its Dependence on Nitrogen Oxides and the Production Rate of Free Radicals - Craig Stroud; Sasha Madronich; Elliot Atlas; Christopher Cantrell; Alan Fried; Brian Wert; Brian Ridley; Fred Eisele; Lee Mauldin; Richard Shetter; Barry Lefer; Frank Flocke; et al. (Journal of Atmospheric Chemistry, 2004)